The distal form of spinal muscular atrophy: an unusual case demonstrating the intermediate variety. Issue 683 (September 1982) - Isenberg, D. A.; Kahn, Pauline A.
Abstract : A 14-year-old boy with a long history of distal muscle weakness affecting primarily and predominantly the upper limbs is described. There is a family history of pes cavus and congenital dislocation of the hip. Electromyography and histopathological studies of skeletal muscle showed conclusive evidence of a neurogenic muscular disorder, and excluded primary muscle disease. The muscle biopsy showed group atrophy. As many target fibres which are identical to structured cores were a prominent feature of the biopsy, central core disease was considered. However, it was concluded on clinical, neurophysiological and histological evidence that the patient was suffering from distal spinal muscular atrophy of an intermediate type designated by previous authors. A review of the current concepts of distal muscle weakness is included.